2016
DOI: 10.1002/2015jb012493
|View full text |Cite
|
Sign up to set email alerts
|

Seismic attenuation structure associated with episodic tremor and slip zone beneath Shikoku and the Kii peninsula, southwestern Japan, in the Nankai subduction zone

Abstract: The three‐dimensional seismic attenuation structure (frequency‐independent Q) beneath southwestern Japan was analyzed using t* estimated by applying the S coda wave spectral ratio method to the waveform data from a dense permanent seismic network. The seismic attenuation (Qp−1) structure is clearly imaged for the region beneath Shikoku, the Kii peninsula, and eastern Kyushu at depths down to approximately 50 km. At depths of 5 to 35 km, the seismic attenuation structure changes at the Median tectonic line and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
4
23
1
Order By: Relevance
“…Evidence includes spatial correlations between recurrence intervals of SSEs and geologic terranes30, between locations of long-term SSEs and LFEs and heterogeneous fluid transport properties in the overlying plate31, and between segment boundaries of short-term SSEs and areas where seismic properties above the megathrust varies sharply32. Our observations add to the growing body of evidence that LFEs occur only under undrained conditions and that a highly metamorphosed, permeable overlying plate inhibits the generation of LFEs.…”
Section: Discussionmentioning
confidence: 52%
“…Evidence includes spatial correlations between recurrence intervals of SSEs and geologic terranes30, between locations of long-term SSEs and LFEs and heterogeneous fluid transport properties in the overlying plate31, and between segment boundaries of short-term SSEs and areas where seismic properties above the megathrust varies sharply32. Our observations add to the growing body of evidence that LFEs occur only under undrained conditions and that a highly metamorphosed, permeable overlying plate inhibits the generation of LFEs.…”
Section: Discussionmentioning
confidence: 52%
“…They suggested that high-V P /V S zones around the plate interface are generated due to the dehydration of fluid from the subducting plate and that LFEs occur due to the increased pore pressure along the plate interface. Kita and Matsubara (2016) estimated a seismic attenuation structure (Q P ) beneath Shikoku and Kii peninsula. The Q P in the central Shikoku seems to be relatively high in the oceanic crust of the subducting plate as well as in the overlying plate.…”
Section: Resultsmentioning
confidence: 99%
“…A constant stress loading rate means that frequent SSEs will occur at fault patches with smaller stress drops. Previous studies have attributed SSE segmentation to spatial variations in fault strength and/or effective normal stress that may be related to stress drop (e.g., Audet & Bürgmann, ; Brudzinski & Allen, ; Kita & Matsubara, ; Nakajima & Hasegawa, ). Numerical simulations using the rate‐ and state‐dependent friction (RSF) law also reproduced SSE segmentation when along‐strike variations in the effective normal stress were applied (Li et al, ; Liu, ).…”
Section: Discussionmentioning
confidence: 99%